Community Empowerment through Menopause Education and Counseling for Housewives' Social Group in Green Serpong 2 Residential Area - Fitriyati Irviana (Abdimas Paspama, 2025)
This community service activity aimed to enhance the knowledge and awareness of menopausal health among housewives in the Green Serpong 2 residential area. The program was conducted through interactive health education, group discussions, and participatory counseling sessions. Many women experience menopause without adequate understanding of the physical and psychological changes that accompany it, which can lead to anxiety and mismanagement of symptoms. Through this activity, participants were guided to recognize the characteristics of menopause, differentiate it from pathological conditions, and adopt a healthy coping strategy. The approach emphasized emotional support, scientific understanding, and open communication within a safe and familiar community environment. The outcomes showed improved participant awareness and readiness to face the menopausal phase with confidence and positivity. This initiative highlights the effectiveness of community-based health education in addressing women's health issues and recommends further implementation of similar programs on a broader scale with support from local health institutions.